Monitoring implementation of the decisions and judgments of the African Commission and Court on Human and Peoples’ Rights (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: It is only relatively recently that attention has been paid to what happens after the African Commission and Court on Human and Peoples’ Rights have issued decisions or judgments, and to the question whether these decisions or judgments actually result in any meaningful change on the ground. Results of a collaborative research project involving desk-based research and interviews with role players on the implementation of the decisions and judgments show that the body monitoring implementation is expected to play various roles. While there has been some movement to establish processes and mechanisms at the regional level to monitor implementation of the Commission and Court’s decisions and judgments, the role that they adopt in monitoring implementation is confused and does not necessarily play to their respective strengths. Perhaps because of this confused state of play, there is an impasse, certainly at the level of the African Commission, in developing further the monitoring of implementation. This article therefore concludes by proposing some pragmatic, low-cost solutions to move monitoring implementation forward on the continent. TITRE ET RÉSUMÉ EN FRANÇAIS: Suivi de la mise en œuvre des décisions et jugements de la Commission africaine et de la Cour africaine des droits de l’homme et des peuples RÉSUMÉ: L’intérêt accordé au sort des décisions ou arrêts rendus par la Commission africaine et la Cour africaine des droits de l’homme et des peuples est récent. Il en est de même en ce qui concerne la question de savoir si ces décisions ou arrêts ont un impact réel. Les résultats d’un projet de recherche collaboratif impliquant une recherche documentaire et des entretiens avec des acteurs sur la mise en œuvre des décisions et des arrêts montrent que l’organe en charge du suivi de la mise en oeuvre devrait jouer différents rôles. Bien qu’il y ait eu un certain engouement pour établir au niveau régional des processus et des mécanismes de suivi des décisions et arrêts de la Commission et de la Cour, le rôle que les deux organes jouent dans le suivi est confus et ne milite pas nécessairement en faveur de leur renforcement respectif. Sans doute du fait de cette situation confuse, il y a une impasse, certainement davantage au niveau de la Commission africaine, de faire avancer le suivi de la mise en œuvre. Cet article conclut par conséquent en proposant des solutions pragmatiques et peu coûteuses pour aller de l’avant dans le suivi de l’exécution des décisions concernées sur le continent.
Keywords: African Court on Human and Peoples’ Rights; African Commission on Human and Peoples’ Rights; implementation; monitoring; decisions; judgments